SELF-CONFIDENCE ANALYSIS STUDY ON MEN’S FUTSAL EXTRACURRICULAR ACTIVITIES AT SMA NEGERI 1 TERISI - Aldi Supriyanto; Citra Resita; Ariya Kusuma Yuda (Journal Physical Education, Health and Recreation, 2022)
The purpose of this study was to determine how big the level of self-confidence in futsal extracurricular students at SMA Negeri 1 Terisi. The subjects of this study were all members of the men's futsal extracurricular at SMA Negeri 1 Terisi, totaling 28 respondents. In this study, the data analysis technique used was descriptive quantitative. The method used in this study is a survey, while the data collection technique on the respondents is using a questionnaire, the questionnaire in this study uses a Likert scale. The results of the study found out how big the level of self-confidence of students who were registered in futsal extracurricular activities at SMA Negeri 1 Terisi was in the "very good" category with a percentage of 7.14% in the "good" category with a percentage of 25%, in the "good enough" category. with a percentage of 35.71% in the "poor category" with a percentage of 28.75% while in the last category "very poor" with a percentage of 3.57%